NIKLAS LUHMANN’S SOCIAL SYSTEMS THEORY: THE ISSUE OF SUBSYSTEM AUTONOMY - Milorad Djuric; Djordje Stojanovic (Srpska Politička Misao)
Niklas Luhmann articulates the basic elements of his authentic theoretical position as criticism of, as he calls them, classical sociology or classical organisation theory. While within these orientations, (social) systems are mainly interpreted as centralised entities whose structures are stabilised by purpose determined at the top, Luhmann, in his general theory of social systems privileges internal differentiation in which subsystems autonomously define their purposes, making society more flexible and capable of responding to environmental challenges. In that sense, the main intention of this paper is the creation of cognitive interest for the notions of complexity and flexibility, i.e. for the issue of subsystem autonomy, as the important elements of Luhmann’s general theory of social systems. Our premise is that the establishment of subsystem autonomy is not a matter of mere, a priori, theoretical and/or practical arbitrariness, nor does it mean an introduction into deconstruction of the system, but it represents a necessary step in the creation of successful responses of the social system to problems arising from the immense and dynamic complexity of its own environment. In other words, through the process of internal differentiation, by establishing subsystem autonomy, the social system increases its own complexity, i.e. ability to adjust to the environment. Thus, challenges arising from the environment are not transferred to the whole, but localised and processed in the appropriate, autonomous parts of the system. By so increasing its internal complexity, the system undeniably acquires the necessary flexibility, or capability for a faster and more efficient creation of alternative.